Australian contributions to tourist behaviour studies. (March 2016) - Pearce, Philip L.
Abstract: It is the purpose of this review to record some of the highlights of the Australian contribution to the global flow of ideas in tourist behaviour research. The context for appreciating the contribution is formulated by recognising the fusion culture of Australian life which effectively provides a meeting ground for ideas from other continents. Four themes, and several strands of ideas within these themes, are presented for national and international consideration. There are well cited studies in tourist motivation, plentiful examples of distinctive topics and tools for appraising tourist markets, insightful approaches to embellishing and assessing on-site experiences, and a broad appreciation of the outcomes of tourism for tourists. The review is approached from the perspective of an active, immersed participant and utilises a wide variety of sources in an attempt to recognise novel concepts and material rather than recycled or locally restricted studies. Many of the research studies are well cited, a recognition that Australians not only have a place in the sun but also offer some rays of light for global friends and colleagues.